Managing Resources - Flint, David (Hodder Headline Group, 1999)
This text examines the world's resources and the ways in which humans manage them. It covers a range of resource issues from energy generation and mineral extraction, to water disputes and sustainable forests, showing how a variety of management strategies work and what problems can arise.
Keywords: Human Geography; Natural Resources; Nature; Social Science